Kombinasi Fermentasi Kotoran Sapi Fermentasi Ampas Tahu dan Fermentasi Limbah Sayur Terhadap Kelimpahan Populasi dan Biomasa Cacing Sutera (Tubifex Sp) - Wiska Yusuf; Syamsuddin; Mulis (Transbahasa, 2024)
The cultivation of tubifex worms (Tubifex sp) traditionally utilizes nearly 100% organic materials as the growing medium; however, this approach has not yielded optimal biomass compared to the use of fermented organic materials. This study aims to evaluate the effectiveness of fermented media in enhancing the population density and biomass of tubifex worms. The study employed a Completely Randomized Design (CRD) with three treatments and four replications. The treatments consisted of different combinations of fermented organic materials, specifically cow manure and tofu waste, with varying proportions in each treatment. Measurements of population density and biomass were conducted after a specified rearing period. The cultivation was carried out in locations proximate to water sources to ensure optimal environmental conditions. The findings indicated that the use of combined fermented organic materials significantly affected the population density and biomass of tubifex worms (Tubifex sp). Treatment A demonstrated the highest population density and biomass, reaching 44.675 grams. These results suggest that fermented media provide a more conducive environment for the growth and reproduction of tubifex worms compared to non-fermented media. The application of fermented media composed of cow manure and tofu waste effectively enhances the population density and biomass of tubifex worms (Tubifex sp). Additionally, conducting cultivation near reliable water sources is crucial for supporting optimal worm growth. Future cultivation practices are recommended to incorporate fermented media and ensure adequate water availability to achieve maximum yield.